Faktor-Faktor Yang Berhubungan Dengan Peningkatan Kasus Stunting Pada Balita Di Kabupaten Probolinggo - Munir, Zainal; Kholisotin, Kholisotin; Hasanah, Ayu Masrurotul (Jurnal Keperawatan Profesional, 2021)
Stunting is the upcoming of indeks condition in the higher level that is based on the age. minus and standar devision according to WHO. Stunting is manifestation with no limition factor of the diet consumer. Who has low quality and also the protein in the growing up development it is started since first life. Planing observation to find factor relation between the case of stunting development since baby in probolinggo regency. This quantitative observation to close sectional cross with sampel election by using random sampling those are 52 respodens. Based on analyze of data that is used by univariat analisa, bivariat usage based on chi square uji. As the result of this observation those are : (1) the relation of mother protein with the improvementof stunting case for the baby with p value 0,003<0,05. (2) the relation of upbringing of stunting case for baby in p value : 0,002<0,05. (3) the relation of economic factor in upbringing stuntinnf case for baby with p value 0,004<0,05 in summary : bored on the relation between variable and stunting case of baby, government observation in society in the healthy instansi job to obigate and practice based of the schedule which given in every groups. This about the importance of protecting dtunting from now.and also it can be more spesific for mother in protecting stunting from now and give more protein for the son to make e qucil.